A feasibility study in adapting Shamos Bickel and Hodges Lehman estimator into T-Method for normalization - Harudin N.; Jamaludin K.R.; Nabil Muhtazaruddin M.; Ramlie F.; Muhamad W.Z.A.W. (Institute of Physics Publishing, 2023)
Errors; Forecasting; Manufacture; Parameter estimation; Classical methods; Classical statistics; Error percentage; Feasibility studies; Mahalanobis-taguchi systems; Mean and standard deviations; Multivariate data; Robust parameters; Population statistics